A three-dimensional model of an articulated frame-steer vehicle for coupled ride and handling dynamic analyses. Issue 3 (2014) - Pazooki, Alireza; Rakheja, Subhash; Cao, Dongpu
The ride and directional stability properties of an articulated frame steer vehicle (ASV) are investigated through formulation of a comprehensive three-dimensional vehicle model. The model integrates a kineto-dynamic formulation of the frame steering system, a torsio-elastic rear axle suspension, and random roughness of two parallel terrain tracks. The validity of the model is illustrated on the basis of the field-measured ride vibration data and steering strut responses to a 90-degree-turn manoeuvre. The model is applied to determine the ride and yaw/roll dynamic responses of an articulated dump truck with and without a rear-axle suspension under steady and transient steering inputs. The ride responses are evaluated in terms of weighted and un-weighted rms accelerations at the operator location, while the directional responses are obtained in terms of static and dynamic rollover thresholds, rearward amplification ratio, and critical speed corresponding to snaking instability. The results suggest that the rear-axle torsio-elastic suspension yields slightly lower yaw and roll stability limit of the vehicle but substantial reductions in the ride vibration levels. Tyre interactions with the rough terrains affect the stability limits in a highly adverse manner. The results suggest that suspension design with greater lateral and torsional stiffness could yield enhanced directional stability limits while preserving the ride performance.